Interaction effects of corporate hedging activities for a multi-risk exposure: evidence from a quasi-natural experiment - Markus Hang; Jerome Geyer-Klingeberg; Andreas W. Rathgeber; Clémence Alasseur; Lena Wichmann (Review of Quantitative Finance and Accounting, 2020)
This study analyzes the interaction effects of corporate hedging activities of electric utility firms facing a manifold risk exposure consisting of several market price risks. We employ 16 recent introductions of markets for trading electricity derivatives as a quasi-natural experiment. The results show that electric utilities generally favor domestic markets for trading electricity derivatives, which might be reduced to their usual high market power and the related good predictability of electricity prices. As a consequence, electricity output hedging eliminates a major part of overall market risk. Further, we identify several spillover effects of electricity output hedging: The sensitivities to input commodity prices decrease, while the sensitivities to foreign exchange rates and interest rates increase. Furthermore, electricity output hedging increases debt capacities and the availability of internal funds. These results are relevant for electric utility firms, market operators, and policy makers, since the selective presence of derivatives markets might let financing policies globally diverge.
Keywords: G32; G38; L94; 330; Corporate hedging; Difference-in-differences; market access; Market introduction; Utility industry